Finite element simulation of creep in swollen Nitril Butadiene Rubber (NBR) pipe under internal pressure / Mohammad Reza Hassan - Mohammad Reza, Hassan (2013)
Elastomers are increasingly used as engineering materials due to their high manufacturability, low weight, low cost and excellent mechanical properties. During the service, elastomer degradation can occur as the result of interaction with the environment. In the case of exposure to aggressive liquids or solvents such as palm biodiesel, degradation in the form of swelling can occur which leads to a reduction in its properties. Nitrile Butadiene Rubber (NBR) is one type of elastomers which is widely used where high oil resistance is required such as in automotive seals, gaskets, or other items subject to contact with oils. The objective of this dissertation is to investigate the effect of swelling on the creep behavior of elastomeric pipe under internal pressure using finite element simulation. For this purpose, the commercial finite element code ANSYS is used to simulate the creep response of dry and swollen NBR. Two swelling levels are considered. During simulation, both dry and swollen elastomers are assumed to be visco-hyperelastic, isotropic and incompressible. The shear relaxation modulus of elastomers is obtained from experimental works conducted by other students. The results showed significant creep on both dry and swollen elastomers. Moreover, it is observed that the creep decreases as the swelling level increases. These results are consistent with the experimental finding in the literature.